DEVELOPMENT OF PBL E-MODULES ON POLYHEDRON CONSTRUCTIONS FOR GEOMETRICAL THINKING ABILITY - Felia Dwi Rahayu; Venissa Dian Mawarsari; Rohmat Suprapto (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
This research aimed to address the issue of low geometry proficiency among students and the lack of teaching materials and assess the validity and practicality of utilizing PBL e-modules as a teaching aid. The research employed the ADDIE model as a development method. To assess the e-module's validity, three media and three material experts were consulted. The material expert evaluation yielded a score of 3.60, while the media expert evaluation yielded a score of 3.29, indicating that the media and material of the e-module are valid for use as teaching materials. Furthermore, a small class trial involving ten students demonstrated a practicality score of 3.35, signifying highly practical results. The field test resulted in a score of 3.25, indicating that the PBL e-module is practical. The teacher's response yielded a score of 3.74, indicating that it is practical. Consequently, the PBL e-modules developed for the geometric material on polyhedron thinking skills are valid and practical, making them suitable as teaching materials in the learning process.